Management & organisational behaviour - Mullins, Laurie J.; Christy, Gill (Pearson Education, 2013)
Presenting a managerial approach to the study of organisational behaviour, with an emphasis on improving working performance through a better understanding of human resources, this book contains summaries, review questions, and assignments.